Discussion on the evolution of public payment policies for environmental services (PES) in Brazilian municipalities - Santos, Rogério Pires (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Most of the natural resources, which provide ecosystem services, are found in rural areas.With the increasing environmental degradation promoted by economic growth and the complete absence of sustainability mechanisms, the pressure exerted by the government on these areas has increased, burdening mainly small rural producers. Parallel to this reality are the Payment for Environmental Services (PES) programs. This workpresents a discussion on the evolution of this mechanism, adopted mainly by Brazilian Municipalities. It addresses the benefits, constitutionality and main obstacles found for itsimplementation and execution by federation entities. Despite the legal provision contained in article 41 of Federal Law 12,651/2012 and in the recent Federal Law 14,119̸2021, the effective implementation of PES programsdonot exist at the federal level. However, about 400 Brazilian municipalities have Municipal Legislation on PES, mostly dealing with the conservation of water resources. Itdemonstrates the viability of this environmental public policy, despite the fear of public managers and the obstaclesassociated with financial viability due to constant economic crises faced by the country.